EXPLORING CRITICAL THINKING ACTIVITIES IN LISTENING COMPREHENSION EXERCISES - Sulistyani, Sulistyani; Khoiriyah, Khoiriyah; Wicaksono, Agung; Aji, Mahendra Puji Permana; Sardanto, Rino (Premise: Journal of English Education and Applied Linguistics, 2023)
This study identifies the critical thinking activities employed in listening comprehension exercises and the way the activities facilitate students' listening comprehension. The study employs content analysis to explore integrating critical thinking activities in listening comprehension exercises. The study involves the listening exercise source, namely a textbook entitled Real Listening and Speakingoye Three by Miles Craven. The result of the study shows that critical thinking activities include identifying the situation and the factors that may influence it, locating the basis for the research that is presented to understand the big picture, learning how to avoid personal biases, and "evaluate information objectively," using the knowledge to make logical inferences, and figuring out what information is the most important and relevant to the situation. Meanwhile, developing the practice of curiosity asking open-ended questions and following up on the answers is not found. The listening skills facilitated by these activities include finding general information, identifying the communicative purpose, finding specific information, and making a conclusion. This study significantly models English teachers to design listening comprehension exercises that promote students' listening comprehension and critical thinking skills.